Effect of Biochar on Soil Greenhouse Gas Emissions at the Laboratory and Field Scales - Fidel, Rivka B.; Laird, David A.; Parkin, Timothy B. (Soil systems, 2019)
Biochar application to soil has been proposed as a means for reducing soil greenhouse gas emissions and mitigating climate change. The effects, however, of interactions between biochar, moisture and temperature on soil CO2 and N2O emissions, remain poorly understood. Furthermore, the applicability of lab-scale observations to field conditions in diverse agroecosystems remains uncertain. Here we investigate the impact of a mixed wood gasification biochar on CO2 and N2O emissions from loess-derived soils using: (1) controlled laboratory incubations at three moisture (27, 31 and 35%) and three temperature (10, 20 and 30 °C) levels and (2) a field study with four cropping systems (continuous corn, switchgrass, low diversity grass mix and high diversity grass-forb mix). Biochar reduced N2O emissions under specific temperatures and moistures in the laboratory and in the continuous corn cropping system in the field. However, the effect of biochar on N2O emissions was only significant in the field and no effect on cumulative CO2 emissions was observed. Cropping system also had a significant effect in the field study, with soils in grass and grass-forb cropping systems emitting more CO2 and less N2O than corn cropping systems. Observed biochar effects were consistent with previous studies showing that biochar amendments can reduce soil N2O emissions under specific but not all, conditions. The disparity in N2O emission responses at the lab and field scales suggests that laboratory incubation experiments may not reliably predict the impact of biochar at the field scale.